Secondary Release of Exosomes from Astrocytes Contributes to the Increase in Neural Plasticity and Improvement of Functional Recovery after Stroke in Rats Treated with Exosomes Harvested from MicroRNA 133b-Overexpressing Multipotent Mesenchymal Stromal Cells - Hongqi Xin Ph.D. (Cell Transplantation, 2017)
We previously demonstrated that multipotent mesenchymal stromal cells (MSCs) that overexpress microRNA 133b (miR-133b) significantly improve functional recovery in rats subjected to middle cerebral artery occlusion (MCAO) compared with naive MSCs and that exosomes generated from naive MSCs mediate the therapeutic benefits of MSC therapy for stroke. Here we investigated whether exosomes isolated from miR-133b-overexpressing MSCs (Ex-miR-133b + ) exert amplified therapeutic effects. Rats subjected to 2 h of MCAO were intra-arterially injected with Ex-miR-133b + , exosomes from MSCs infected by blank vector (Ex-Con), or phosphate-buffered saline (PBS) and were sacrificed 28 days after MCAO. Compared with the PBS treatment, both exosome treatment groups exhibited significant improvement of functional recovery. Ex-miR-133b + treatment significantly increased functional improvement and neurite remodeling/brain plasticity in the ischemic boundary area compared with the Ex-Con treatment. Treatment with Ex-miR-133b + also significantly increased brain exosome content compared with Ex-Con treatment. To elucidate mechanisms underlying the enhanced therapeutic effects of Ex-miR-133b + , astrocytes cultured under oxygen- and glucose-deprived (OGD) conditions were incubated with exosomes harvested from naive MSCs (Ex-Naive), miR-133b downregulated MSCs (Ex-miR-133b − ), and Ex-miR-133b + . Compared with the Ex-Naive treatment, Ex-miR-133b + significantly increased exosomes released by OGD astrocytes, whereas Ex-miR-133b − significantly decreased the release. Also, exosomes harvested from OGD astrocytes treated with Ex-miR-133b + significantly increased neurite branching and elongation of cultured cortical embryonic rat neurons compared with the exosomes from OGD astrocytes subjected to Ex-Con. Our data suggest that exosomes harvested from miR-133b-overexpressing MSCs improve neural plasticity and functional recovery after stroke with a contribution from a stimulated secondary release of neurite-promoting exosomes from astrocytes.